2021
DOI: 10.3389/fcimb.2021.748558
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Microbiome and Transcriptome Data Reveals the Interplay Between Commensal Bacteria and Fibrin Degradation in Endometrial Cancer

Abstract: The gut-uterus axis plays a pivotal role in the pathogenesis of endometrial cancer (EC). However, the correlations between the endometrial microbiome and endometrial tumor transcriptome in patients with EC and the impact of the endometrial microbiota on hematological indicators have not been thoroughly clarified. In this prospective study, endometrial tissue samples collected from EC patients (n = 30) and healthy volunteers (n = 10) were subjected to 16S rRNA sequencing of the microbiome. The 30 paired tumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 56 publications
(71 reference statements)
1
29
1
Order By: Relevance
“…Hence, Prevotella may promote fibrin degradation by inducing the expression of specific genes. Moreover, the authors propose that their identity could be used to predict or diagnose endometrial cancer (Li et al 2021).…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Hence, Prevotella may promote fibrin degradation by inducing the expression of specific genes. Moreover, the authors propose that their identity could be used to predict or diagnose endometrial cancer (Li et al 2021).…”
Section: Endometrial Cancermentioning
confidence: 99%
“…As shown by other studies available in the literature, Porphyromonas sp. have previously been isolated intracellularly, and it is possible that they are capable of interfering with normal cellular regulatory processes and, thus, triggering the process of carcinogenesis [ 60 , 61 , 62 ].…”
Section: Composition Of the Endometrial And Uterine Microbiota In Pat...mentioning
confidence: 99%
“…in endometrial lesions may play a putative role in the development of endometrial cancer [ 43 ]. Moreover, the team of Li et al in 2021, showed that the advanced severity of the disease is associated with a reduction in the diversity of the endometrial microbiome [ 62 ]. After completing their transcriptome research, they found altered expression of genes associated with fibrin breakdown in endometrial tumor tissues.…”
Section: Composition Of the Endometrial And Uterine Microbiota In Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. reported that the proportions of Prevotella, Muribaculum Pelomonas and Nocardioides in EC patients were higher than those in healthy people, while the proportion of Oscillibacter was lower ( 170 ). Walther-antonio et al.…”
Section: Endometrial Microbial Composition and Immune Characteristics...mentioning
confidence: 99%